Social computing and social media : user experience and behavior : 10th International Conference, SCSM 2018, held as part of HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings.: user experience and behavior : 10th International Conference, SCSM 2018, held as part of HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings. Part I (2018) - Unknown
No abstract available